Zwitterionic organic compounds, additives for polyimides, polyamic acid syrup, polyimides

CN122831828APending Publication Date: 2026-09-29YONGJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611081302.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

聚酰胺酸的热酰亚胺化过程中,羧基与酰胺基缩合生成酰亚胺环并释放水,水的存在会导致薄膜内部气泡、表面针孔等缺陷,同时残留水分作为极性介质会提高材料的介电常数和介电损耗,影响材料的绝缘性能

Benefits of technology

[0017]本申请的附加方面和优点将在下面的描述中部分给出,部分将从下面的描述中变得明显,或通过本申请的实践了解到。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a zwitterionic organic compound, an additive for polyimide, a polyamic acid slurry and a polyimide, and belongs to the technical field of polyimide materials. The zwitterionic organic compound comprises a quaternary ammonium zwitterion structure symmetrically located on both sides of the center of a molecule; the quaternary ammonium zwitterion structure satisfies the following conditions: (a) having a quaternary ammoniumized tertiary amine positive center; (b) having an imide type negative center; and (c) having at least one hydroxyl group. The zwitterionic organic compound provided by the application has the specific quaternary ammonium zwitterion structure described above, is endowed with multiple functions such as catalysis-crosslinking-dehydration, and can be applied to a polyamic acid slurry as an amine imide additive, so that the polyamic acid slurry is inert at room temperature and is thermally decomposed after heating, and under the premise of ensuring the storage stability of the polyamic acid slurry, imidization is realized at a low temperature and with high efficiency, a highly crosslinked network is constructed, and the adverse effects caused by dehydration are eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polyimide materials technology, specifically to an amphoteric organic compound, an additive for polyimide, a polyamic acid slurry, and polyimide. Background Technology

[0002] Polyimide (PI) is widely used in microelectronics, flexible printed circuit boards, aerospace, and optoelectronic devices due to its excellent heat resistance, mechanical properties, electrical insulation properties, and chemical stability. In the processing of polyimide products, a solution or slurry of its precursor, polyamic acid (PAA), is typically prepared first, and then an imidization reaction is carried out through heating or chemical methods to ultimately form the polyimide product.

[0003] As electronic devices evolve towards thinner profiles, higher integration, and greater flexibility, higher demands are placed on the comprehensive performance of polyimide materials, particularly in terms of mechanical properties, thermal stability, dielectric properties, and processing adaptability. During the thermal imidization of polyamic acid, the carboxyl and amide groups condense to form an imide ring and release water. The presence of water can lead to defects such as internal bubbles and surface pinholes in the film. Furthermore, residual moisture, acting as a polar medium, increases the dielectric constant and dielectric loss of the material, affecting its insulation performance. In addition, the imidization reaction of polyamic acid typically requires high temperatures (above 300°C), and the thermal stress accumulated during high-temperature curing is becoming increasingly prominent, creating an urgent need for low-temperature curing technology.

[0004] Therefore, how to achieve low-temperature and efficient imidization while ensuring the storage stability of polyamic acid slurry, and at the same time construct a highly cross-linked network and eliminate the adverse effects of dehydration, has become a technical problem that urgently needs to be solved in this field.

[0005] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention

[0006] In a first aspect of this application, an amphoteric organic compound is proposed, comprising a quaternary ammonium zwitterionic structure symmetrically located on both sides of the molecular center; The quaternary ammonium zwitterion structure satisfies the following condition: (a) It has a positively charged quaternary ammonium amine center; (b) It has an imide-type negative charge center; (c) It has at least one hydroxyl group.

[0007] The zwitterionic organic compound provided in this application has the aforementioned specific quaternary ammonium zwitterionic structure, endowing it with multiple functions such as catalysis, crosslinking, and dehydration. It can be applied to polyamic acid slurry as an amino imide additive, making it inert at room temperature and thermally decomposed upon heating. Under the premise of ensuring the storage stability of polyamic acid slurry, it can achieve low-temperature and efficient imidization, while constructing a highly crosslinked network and eliminating the adverse effects of dehydration, thus making up for the shortcomings of the prior art.

[0008] In some embodiments, the zwitterionic organic compound includes compounds with the following general chemical formula: R1R2R3N + -N - -C(O)-R4-C(O)-N - -N + R1R2R3; The quaternary ammonium zwitterion structure is R1R2R3N. + -N - -C(O)-, R1, R2, and R3 are each independently an alkyl group containing a secondary hydroxyl group; R4 is a divalent organic group.

[0009] In some embodiments, R1, R2, and R3 each independently include a C2-C8 alkyl group containing a secondary hydroxyl group, wherein the C2-C8 alkyl group containing a secondary hydroxyl group includes 2-hydroxypropyl, 3-hydroxybutyl, 2-hydroxybutyl, 3-hydroxypentyl, 2-hydroxypentyl, 4-hydroxyhexyl, 3-hydroxyhexyl, 2-hydroxyhexyl, 5-hydroxyheptyl, 4-hydroxyheptyl, 3-hydroxyheptyl, 2-hydroxyheptyl, 6-hydroxyoctyl, 5-hydroxyoctyl, 4-hydroxyoctyl, 3-hydroxyoctyl, and 2-hydroxyoctyl. And / or, the R4 includes C1-C10 alkylene, arylene, and alicyclic groups, wherein the C1-C10 alkylene includes ethylene and propylene, the arylene includes p-phenylene, and the alicyclic group includes cyclohexamethylene.

[0010] In some embodiments, the zwitterionic organic compound includes compounds represented by the following chemical formulas: Compound 1: [(HOCH2CH2)2N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 2: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4; Compound 3: [(HOCH(CH2CH3)CH2)2N+ (CH3)-N - -C(=O)]2-(CH2)4; Compound 4: [(HOCH(CH3)CH2)(HOCH(CH3)CH2)N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 5: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)2; Compound 6: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-C6H4; Compound 7: [(HOCH(CH3)CH2CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4.

[0011] In some embodiments, the zwitterionic organic compound has thermally reversible decomposition characteristics; And / or; the thermally reversible decomposition temperature of the zwitterionic organic compound is 120℃-180℃; And / or, the thermally reversible decomposition products of the zwitterionic organic compounds include polyhydroxy tertiary amines and diisocyanates.

[0012] In a second aspect of this application, an additive for polyimides is provided, comprising the zwitterionic organic compound described in the first aspect. Thus, this additive for polyimides possesses all the characteristics and advantages of the aforementioned zwitterionic organic compound, which will not be repeated here.

[0013] In a third aspect, this application provides a polyamic acid slurry comprising the zwitterionic organic compound described in the first aspect. Consequently, this polyamic acid slurry exhibits excellent storage stability and enables low-temperature, efficient imidization, while simultaneously constructing a highly cross-linked network and eliminating the adverse effects of dehydration.

[0014] In some embodiments, by parts by weight, it includes: 100 parts by weight of polyamic acid, 0.1 to 15 parts by weight of the zwitterionic organic compound, and 150 to 500 parts by weight of solvent.

[0015] In some embodiments, the raw materials for the polyamic acid include dianhydride monomers and diamine monomers. The dianhydride monomers include at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and 4,4'-oxobisphthalic anhydride. The diamine monomers include at least one of 4,4'-diaminodiphenyl ether and p-phenylenediamine. And / or, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0016] In a fourth aspect of this application, a polyimide is proposed, which is obtained by curing the polyamic acid slurry described in the third aspect. As a result, the density of this polyimide material is significantly improved, it is free of pinholes and bubbles, and its tensile strength, elongation at break, thermal decomposition temperature, dimensional stability, and insulation properties are all significantly improved, solving the problems of brittleness, porosity, and poor stability of traditional polyimides.

[0017] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation

[0018] The embodiments of this application are described in detail below, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.

[0019] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit the application; unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.

[0020] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.

[0021] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that the ranges 60-110 and 80-120 will also be understood.

[0022] In the description of this application, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. "First feature" and "second feature" may include one or more of that feature.

[0023] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] In a first aspect of this application, an amphoteric organic compound is proposed, comprising a quaternary ammonium zwitterionic structure symmetrically located on both sides of the molecular center; The quaternary ammonium zwitterion structure satisfies the following condition: (a) It has a positively charged quaternary ammonium amine center; (b) It has an imide-type negative charge center; (c) It has at least one hydroxyl group.

[0027] The zwitterionic organic compound provided in this application has the aforementioned specific quaternary ammonium zwitterionic structure, endowing it with multiple functions such as catalysis, crosslinking, and dehydration. It can be applied to polyamic acid slurry as an amino imide additive, making it inert at room temperature and thermally decomposed upon heating. Under the premise of ensuring the storage stability of polyamic acid slurry, it can achieve low-temperature and efficient imidization, while constructing a highly crosslinked network and eliminating the adverse effects of dehydration, thus making up for the shortcomings of the prior art.

[0028] In some embodiments, the zwitterionic organic compound includes compounds with the following general chemical formula: R1R2R3N + -N - -C(O)-R4-C(O)-N - -N + R1R2R3; The quaternary ammonium zwitterion structure is R1R2R3N. + -N - -C(O)-, R1, R2, and R3 are each independently an alkyl group containing a secondary hydroxyl group; R4 is a divalent organic group. Therefore, the zwitterionic organic compound has a bi-terminated symmetrical polyhydroxylamine imide structure, exhibiting a stable inner salt structure at room temperature. It demonstrates excellent compatibility with polyimide slurries and does not affect the slurry's storage stability. It undergoes controlled, directional decomposition at high temperatures with no byproduct residue, making it suitable for polyimide gradient curing processes. Simultaneously, the pyrolysis products of a single molecule achieve a triple functional integration of catalysis, crosslinking, and dehydration: the tertiary amine catalyzes the imidization reaction of polyamic acid (lowering the curing temperature); the polyhydroxyl groups of the tertiary amine undergo multiple esterification crosslinking with the carboxyl groups of polyamic acid (constructing a three-dimensional network); and the diisocyanate in situ captures the water generated during imidization (eliminating defects and generating an active diamine for further crosslinking).

[0029] In some embodiments, R1, R2, and R3 each independently include a C2-C8 alkyl group containing a secondary hydroxyl group, wherein the C2-C8 alkyl group containing the secondary hydroxyl group includes 2-hydroxypropyl, 3-hydroxybutyl, and 2-hydroxybutyl. This ensures that the group stably carries the secondary hydroxyl group without steric hindrance or shielding effects.

[0030] In some embodiments, R4 comprises C1-C10 alkylene, arylene, and alicyclic groups; the C1-C10 alkylene comprises ethylene and propylene; the arylene comprises p-phenylene; and the alicyclic group comprises cyclohexamethylene. This facilitates adaptation to polyamic acid slurry systems, ensuring a balance between the flexibility and rigidity of the molecular chains.

[0031] In some embodiments, the zwitterionic organic compound includes compounds represented by the following chemical formulas: Compound 1: [(HOCH2CH2)2N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 2: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4; Compound 3: [(HOCH(CH2CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4; Compound 4: [(HOCH(CH3)CH2)(HOCH(CH3)CH2)N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 5: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)2; Compound 6: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-C6H4; Compound 7: [(HOCH(CH3)CH2CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4.

[0032] In some embodiments, the zwitterionic organic compound has thermally reversible decomposition characteristics; thus, it has a latent characteristic: it is inert at room temperature in polyamic acid slurry and thermally decomposes upon heating.

[0033] In some embodiments, the method for preparing the zwitterionic organic compound includes the following steps. In a dry 500 mL three-necked flask, add dimethyl dicarboxylic acid (0.10 mol), substituted hydrazine (0.20-0.22 mol, i.e., 2.0-2.2 equivalents; for example, 2.1 equivalents), and anhydrous ethanol (200-300 mL, for example, 240 mL, 260 mL, etc.) in sequence. Adding a slightly excessive amount of substituted hydrazine (2.0-2.2 equivalents, for example, 2.1 equivalents) promotes complete reaction and increases yield.

[0034] Sodium methoxide (0.005-0.01 mol, i.e., 5-10 mol% of the feed amount, for example, 8 mol%) is added as a catalyst under nitrogen protection. Sodium methoxide can effectively promote the ammonolysis reaction of esters and shorten the reaction time. If the steric hindrance of the substituted hydrazine is large, the amount of catalyst can be appropriately increased to 10-15 mol% (for example, 12 mol%).

[0035] Heat the reaction system to 75-80℃ (e.g., 78℃) and reflux for 18-24 hours (e.g., 20 hours). During the reaction, the system gradually changes from turbid to clear, indicating that the amidation reaction is underway. For R 4As a substrate for aromatic compounds (such as terephthalates), the reactivity is slightly lower, and the reaction time can be extended to 24-30 hours (e.g., 26 hours), or the temperature can be appropriately increased to 80-85℃ (e.g., 82℃).

[0036] The reaction process can be monitored by thin-layer chromatography (TLC) (developing solvent: ethyl acetate / methanol = 5:1, iodine tank for color development), or the reaction endpoint can be determined by observing the amount of methanol / ethanol distilled off as byproducts.

[0037] After the reaction was completed, the ethanol was removed by vacuum evaporation (water bath temperature ≤50℃, vacuum degree ≈0.095 MPa), yielding a viscous residue.

[0038] The residue was dissolved in an appropriate amount of ethyl acetate, and n-hexane was slowly added dropwise until the mixture became slightly turbid. After standing overnight, white or pale yellow crystals precipitated. The crystals were filtered, washed with a small amount of ethyl acetate-n-hexane (1:2) mixed solvent, and dried under vacuum (50-60°C, for example, 55°C; 12 hours) to obtain the target product.

[0039] In some embodiments, the thermally reversible decomposition temperature of the zwitterionic organic compound is 120°C-180°C, for example, it can be 120°C, 140°C, 150°C, 160°C, 180°C or any range between the aforementioned values; the thermal decomposition temperature of the NN bond can be precisely adjusted by controlling the molecular structure of the additive, so that its decomposition temperature window (80°C-150°C) is well matched with the imidization reaction window of polyamic acid, ensuring that the active species are released in a timely manner during the imidization process, and achieving maximum efficiency.

[0040] In some embodiments, the thermally reversible decomposition products of the zwitterionic organic compound include polyhydroxy tertiary amine compounds and diisocyanate compounds. Therefore, by utilizing the preferential reaction of diisocyanates with water, the adverse effects of water generation during imidization are eliminated at the source, effectively reducing defects such as internal bubbles and surface pinholes in the film, lowering dielectric loss, and significantly improving insulation performance and the quality of the polyimide film.

[0041] In a second aspect of this application, an additive for polyimides is proposed, comprising the zwitterionic organic compound described in the first aspect. Thus, this additive for polyimides possesses all the characteristics and advantages of the aforementioned zwitterionic organic compound, such as stability at room temperature, decomposition within the curing temperature range of the polyimide precursor, and multifunctionality including catalytic imidization, multiple crosslinking, and in-situ dehydration, which will not be elaborated further here.

[0042] In this application, the polyimide additive (or aminoimide additive) is a latent multifunctional additive applied to polyimide systems, and has at least the following characteristics: 1) Latent characteristics: The polyimide additive is inert at room temperature in polyamic acid slurry and decomposes thermally upon heating.

[0043] 2) Synergistic effect: This polyimide additive achieves catalytic imidization and multiple crosslinking simultaneously through the presence of secondary hydroxyl tertiary amines, and in-situ dehydration and further crosslinking through diisocyanate, forming a synergistic enhancement system with "one agent, multiple effects". 3) Precise temperature matching feature: This application can precisely adjust the thermal decomposition temperature of the NN bond by controlling the chain length and structure of the group, so that its decomposition temperature window (80-150℃) is well matched with the imidization reaction window of polyamic acid, thereby realizing the timely release of active species.

[0044] 4) In-situ dehydration function: This application is the first to utilize the diisocyanate generated by the pyrolysis of aminoimides to preferentially react with water, thereby eliminating the adverse effects of water generated by imidization from the source and solving the dehydration problem that has long plagued the preparation of polyimide films.

[0045] In a third aspect of this application, a polyamic acid slurry is provided, comprising the zwitterionic organic compound described in the first aspect. Therefore, this polyamic acid slurry exhibits excellent storage stability and enables low-temperature, high-efficiency imidization, while simultaneously constructing a highly cross-linked network and eliminating the adverse effects of dehydration. Specifically, the core mechanism by which the zwitterionic organic compound is used as an additive in polyamic acid slurry includes: 1. Multiple hydroxyl crosslinking reinforcement: The tertiary amine generated by pyrolysis carries multiple secondary hydroxyl groups, which can undergo multi-site esterification crosslinking reactions with a large number of carboxyl groups on the polyamic acid molecular chain, breaking the traditional single crosslinking mode, constructing a three-dimensional dense crosslinking network, and significantly improving the mechanical strength and toughness of the material. 2. In-situ water removal to eliminate defects: The trace amount of water generated during the curing process of polyamic acid cyclization will preferentially react with the diisocyanate generated by pyrolysis, completely consuming the free water in the system, eliminating molding defects such as bubbles, pinholes, and micropores from the source, and improving the density of the material. 3. Secondary crosslinking deep modification: Diisocyanate reacts with water to generate primary amine small molecules. The highly active amine groups of the newly generated primary amine can further undergo amidation crosslinking with the carboxyl groups and incompletely cyclized amide groups of polyamic acid, thereby reinforcing the crosslinking network and further improving the thermal and dimensional stability of the material.

[0046] In some embodiments, by parts by weight, it includes: 100 parts by weight of polyamic acid, 0.1 to 15 parts by weight of the zwitterionic organic compound, and 150 to 500 parts by weight of solvent.

[0047] In this application, the mass fraction of the zwitterionic organic compound can be 0.1 parts by mass, 0.5 parts by mass, 2 parts by mass, 5 parts by mass, 8 parts by mass, 10 parts by mass, 12 parts by mass, 14 parts by mass, 15 parts by mass, or any of the aforementioned values, preferably 1 part by mass to 10 parts by mass.

[0048] In this application, the mass fraction of the solvent may be 150 parts by mass, 200 parts by mass, 220 parts by mass, 300 parts by mass, 400 parts by mass, 450 parts by mass, 500 parts by mass, or any range between the aforementioned values; the solvent may be a polar aprotic solvent, such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, etc.

[0049] In some embodiments, the raw materials for the polyamic acid include dianhydride monomers and diamine monomers. The dianhydride monomers include at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and 4,4'-oxobisphthalic anhydride. The diamine monomers include at least one of 4,4'-diaminodiphenyl ether and p-phenylenediamine. And / or, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0050] In a fourth aspect of this application, a polyimide is proposed, which is obtained by curing the polyamic acid slurry described in the third aspect. As a result, the density of this polyimide material is significantly improved, it is free of pinholes and bubbles, and its tensile strength, elongation at break, thermal decomposition temperature, dimensional stability, and insulation properties are all significantly improved, solving the problems of brittleness, porosity, and poor stability of traditional polyimides.

[0051] In some embodiments, the preparation of polyimide by curing the polyamic acid slurry described in the third aspect includes the following process: S1. Under an inert atmosphere at room temperature, dissolve polyamic acid resin in a polar aprotic solvent, stir evenly, and prepare a polyamic acid base slurry with a solid content of 1%-30% (for example, it can be 1%, 10%, 15%, 20%, 30% or any range between the aforementioned values, etc.). S2. Add the aforementioned polyimide additive (or aminoimide additive) to the polyamic acid-based slurry, stir at a uniform speed for 30-60 minutes (e.g., 30 minutes, 32 minutes, 35 minutes, 40 minutes, 60 minutes or any range between the aforementioned values), and ultrasonically disperse for 10-20 minutes (e.g., 10 minutes, 12 minutes, 15 minutes, 18 minutes, 20 minutes or any range between the aforementioned values) to obtain a uniform and stable modified polyimide slurry; S3. Allow the modified slurry to stand to degas, then cure it with a gradient temperature increase. The gradient temperature increase program is as follows: pre-baking at 80℃-100℃ (e.g., 80℃, 85℃, 90℃, 100℃ or any range between the aforementioned values), medium-temperature cross-linking at 120℃-180℃ (e.g., 120℃, 135℃, 150℃, 180℃ or any range between the aforementioned values), and high-temperature imidization at 200℃-300℃ (e.g., 200℃, 245℃, 280℃, 300℃ or any range between the aforementioned values) to complete the curing and molding.

[0052] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.

[0053] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0054] Example 1 This embodiment provides an amphoteric organic compound (or aminoimide additive), the preparation method of which includes: In a 500 mL three-necked flask, dimethyl adipate (17.4 g, 0.10 mol), 1,1-bis(2-hydroxyethyl)-ethylhydrazine (29.6 g, 0.20 mol), and anhydrous ethanol (200 mL) were added. Sodium methoxide (0.54 g, 0.01 mol) was added under nitrogen protection, and the mixture was refluxed at 75 °C for 20 hours. After the reaction was complete, the ethanol was removed by vacuum distillation, and the residue was recrystallized from ethyl acetate-n-hexane to give a white solid product in 78% yield.

[0055] The chemical formula of the zwitterionic organic compound obtained in this embodiment is shown below: [(HOCH2CH2)2N + (CH2CH3)-N - -C(=O)]2-(CH2)4.

[0056] The characterization test data of the zwitterionic organic compounds obtained in this embodiment are shown below: FTIR (KBr, cm⁻¹) -1 ): 3400 (-OH), 1705 (C=O), 1560 (N + -N - Characteristic absorption). ¹H NMR (D₂O, δ): 3.2–3.9 (m, 20H, -N)+ -CH2- and -CH-OH), 2.4-2.6 (m, 4H, -CO-CH2-), 1.5-1.7 (m, 4H, -CH2-CH2-), 3.0 (s, 6H, N + -CH3).

[0057] Example 2 This embodiment provides a polyamic acid slurry, the composition of which and its preparation method include: Under nitrogen protection, pyromellitic dianhydride (PMDA, 21.8 g, 0.10 mol) and 4,4'-diaminodiphenyl ether (ODA, 20.0 g, 0.10 mol) were subjected to a polycondensation reaction in N-methylpyrrolidone (NMP, 300 g) and stirred at room temperature for 24 hours to obtain a polyamic acid solution with a solid content of about 12%.

[0058] Add the aminoimide additive (2.5g, accounting for 5% of the solid content of polyamic acid) prepared in Example 1 to the above polyamic acid solution, stir at room temperature for 2 hours until completely dissolved, filter and degas to obtain a uniform and stable polyimide slurry.

[0059] Example 3 This embodiment provides a polyimide film, the preparation method of which includes: The polyimide slurry prepared in Example 2 was uniformly coated onto a glass substrate and then placed in an oven for step curing. First stage: 100℃×1 hour, 150℃×1 hour (thermal decomposition of amino imide, catalytic imidization, multiple cross-linking and in-situ dehydration stage). Second stage: 200℃×1 hour, 250℃×1 hour, 350℃×1 hour (complete imidization stage).

[0060] After natural cooling, the film is peeled off from the substrate to obtain a polyimide film with a thickness of about 50 μm.

[0061] Example 4 This embodiment provides an amphoteric organic compound, a polyamic acid slurry, and a polyimide film, which differs from Embodiment 3 in that: (1) The zwitterionic organic compound in Example 1 was modified to a zwitterionic organic compound with the following chemical formula: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4.

[0062] Characterization tests showed that FTIR (KBr, cm⁻¹) was used to detect the following: -¹): 3420 (-OH), 1708 (C=O), 1555 (N + -N - Characteristic absorption). ¹H NMR (D₂O, δ): 3.8–4.2 (m, 4H, -CH-OH), 3.0–3.5 (m, 8H, -N). + -CH2-), 2.4-2.6 (m, 4H, -CO-CH2-), 1.5-1.7 (m, 4H, -CH2-CH2-), 3.05 (s, 6H, N + -CH3), 1.15-1.25 (d, 12H, -CH3).

[0063] Example 5 This embodiment provides an amphoteric organic compound, a polyamic acid slurry, and a polyimide film, which differs from Embodiment 3 in that: (1) The zwitterionic organic compound in Example 1 was modified to a zwitterionic organic compound with the following chemical formula: [(HOCH(CH2CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4.

[0064] Characterization tests showed that FTIR (KBr, cm⁻¹) was used to detect the following: - ¹): 3425 (-OH), 1705 (C=O), 1558 (N + -N - Characteristic absorption). ¹H NMR (D₂O, δ): 3.7–4.0 (m, 4H, -CH-OH), 3.0–3.5 (m, 8H, -N) + -CH2-), 2.4-2.6 (m, 4H, -CO-CH2-), 1.5-1.8 (m, 8H, -CH2-CH2- and -CH2-CH3), 3.05 (s, 6H, N + -CH3), 0.95-1.05 (t, 12H, -CH3).

[0065] Example 6 This embodiment provides an amphoteric organic compound, a polyamic acid slurry, and a polyimide film, which differs from Embodiment 3 in that: (1) The zwitterionic organic compound in Example 1 was modified to a zwitterionic organic compound with the following chemical formula: [(HOCH(CH3)CH2)(HOCH(CH3)CH2)N + (CH2CH3)-N - -C(=O)]2-(CH2)4.

[0066] Characterization tests showed that FTIR (KBr, cm⁻¹) was used to detect the following: - ¹): 3415 (-OH), 1706 (C=O), 1556 (N + -N - Characteristic absorption). ¹H NMR (D₂O, δ): 3.8–4.2 (m, 4H, -CH-OH), 3.0–3.6 (m, 12H, -N). + -CH2- and -N + -CH2CH3), 2.4-2.6 (m, 4H, -CO-CH2-), 1.5-1.7 (m, 4H, -CH2-CH2-), 1.15-1.25 (d, 12H, -CH3), 1.05-1.15 (t, 6H, -CH2CH3).

[0067] Test Example 1 This test example tested the polyimide film obtained in the above examples, and used a film prepared from the same polyamic acid solution without added aminoimide additives as a comparative example. The test results are shown in Table 1. The following methods were used for each performance test: 1. Tensile strength test: The tensile strength of the polyimide film in this invention was measured using an Instron 34TM-5 universal testing machine.

[0068] Method: Thin film samples were cut into dumbbell shapes (length ≥ 30 mm, effective width 5 mm) and tested at room temperature with a tensile rate of 10 mm / min. The maximum tensile load at fracture was recorded. At least five specimens were tested for each sample, and the average value was taken. Tensile strength was calculated using the following formula: Tensile strength (MPa) = F / S Where F is the maximum tensile load (N) and S is the initial cross-sectional area of ​​the specimen (mm²).

[0069] Judgment criteria: Higher tensile strength indicates better mechanical properties of the material. In the embodiments of the present invention, the tensile strength of the polyimide film with added aminoimide additives is 185 MPa, which is significantly better than that of the comparative example without additives (145 MPa). This indicates that the multiple cross-linking function of the additives of the present invention effectively constructs a three-dimensional network structure and significantly improves the mechanical properties of the material.

[0070] 2. Elongation at break test: The elongation at break of the polyimide film in this invention was measured using an Instron 34TM-5 universal testing machine.

[0071] Method: Thin film samples were cut into dumbbell shapes (length ≥ 30 mm, effective width 5 mm) and tested at room temperature with a tensile rate of 10 mm / min. The gauge length at break was recorded. At least five samples were tested for each specimen, and the average value was taken. The elongation at break was calculated using the following formula: Elongation at break (%) = (L1 - L0) / L0 × 100% Where L0 is the initial gauge length of the specimen (mm), and L1 is the gauge length when the specimen breaks (mm).

[0072] Judgment criteria: A moderate elongation at break (≥20%) indicates that the material possesses both good strength and toughness. In the embodiments of this invention, the polyimide film with added aminoimide additives has an elongation at break of 35%, which is better than the comparative example without additives (28%), indicating that the additives of this invention improve the material's strength without sacrificing its toughness.

[0073] 3. Glass transition temperature test: The glass transition temperature (Tg) of the polyimide film in this invention was measured using a DSC2500 differential scanning calorimeter from TA Instruments.

[0074] Method: Take 5-10 mg of film sample and place it in an aluminum sealed crucible. Under nitrogen atmosphere, heat it from room temperature to 400℃ at a heating rate of 10℃ / min. Record the heat flow curve and take the inflection point temperature of the second heating curve as Tg.

[0075] Judgment criteria: A higher Tg indicates a greater crosslinking density and better thermal stability of the material. In the embodiments of the present invention, the Tg of the polyimide film with added aminoimide additives is 285℃, which is significantly better than that of the comparative example without additives (268℃), indicating that the multiple crosslinking function of the additives of the present invention effectively improves the crosslinking density and thermal stability of the material.

[0076] 4. Thermal decomposition temperature Td5% test: Instrument: Thermogravimetric analyzer (TA Instruments TGA5500 or similar) Sample preparation: Cut the polyimide film into small fragments (about 2-5 mg), dry them under vacuum at 80°C for 12 hours to remove moisture and residual solvent, weigh them accurately, and place them in a platinum or alumina sample dish for testing.

[0077] Test conditions: Atmosphere: Nitrogen (N2), flow rate 60 mL / min; heating rate: 10℃ / min; temperature range: room temperature to 800℃.

[0078] Measurement procedure: Preheat the thermogravimetric analyzer to a stable state. After running the baseline under no-load conditions, place the sample pan containing the sample on the balance and close the furnace. Heat the sample from room temperature to 800℃ at a heating rate of 10℃ / min under a nitrogen atmosphere. Continuously record the change in sample mass with temperature to obtain the thermogravimetric (TG) curve.

[0079] Evaluation metrics: The 5% thermogravimetric temperature (Td, 5%) is defined as the temperature at which the sample mass loss reaches 5% of its initial mass. A higher temperature indicates better thermal stability of the material. The 10% thermogravimetric temperature (Td, 10%) and the char residue at 800℃ can also be recorded.

[0080] 5. Dielectric constant test: The dielectric constant of the polyimide film in this invention was determined using an Agilent E4991A impedance analyzer.

[0081] Method: Gold electrodes (approximately 20 mm in diameter) were deposited on both sides of the thin film sample by vapor deposition, and the dielectric constant was measured at 1 MHz and room temperature. At least three samples were tested for each sample, and the average value was taken.

[0082] Judgment criteria: The lower the dielectric constant (≤3.5), the better the insulation performance of the material. In the embodiments of the present invention, the dielectric constant of the polyimide film with added aminoimide additive is 3.2, which is better than that of the comparative example without additive (3.5). This indicates that the in-situ dehydration function of the additive of the present invention effectively reduces the residual moisture in the film and avoids the increase in dielectric constant caused by water molecules as a highly polar medium.

[0083] 6. Dielectric loss test: The dielectric loss factor of the polyimide film in this invention was measured using an Agilent E4991A impedance analyzer.

[0084] Method: Gold electrodes (approximately 20 mm in diameter) were deposited on both sides of the thin film sample by vapor deposition. The dielectric loss factor was measured at 1 MHz and room temperature. At least three samples were tested for each sample, and the average value was taken.

[0085] Judgment criteria: The lower the dielectric loss factor (≤0.01), the better the insulation performance of the material. In the embodiments of the present invention, the dielectric loss of the polyimide film with added aminoimide additive is 0.008, which is significantly better than that of the comparative example without additive (0.015). This indicates that the in-situ dehydration function of the additive of the present invention effectively eliminates the moisture generated during imidization and avoids the increase in dielectric loss caused by residual moisture as a polar medium.

[0086] 7. Water absorption rate test: The water absorption rate of the polyimide film in this invention is determined by the immersion method.

[0087] Method: Dry the film sample (2cm×2cm) in a vacuum oven at 100℃ for 12 hours until constant weight, and weigh it (W0). Then, immerse the sample in deionized water at 25℃ for 24 hours, remove it, blot the surface moisture with filter paper, and weigh it quickly (W1). Calculate the water absorption rate. At least three samples should be tested for each sample, and the average value should be taken. The water absorption rate is calculated using the following formula: Water absorption rate (%) = (W1 - W0) / W0 × 100% Judgment criteria: The lower the water absorption rate (≤2%), the better the moisture resistance of the material. In the embodiments of the present invention, the water absorption rate of the polyimide film with added aminoimide additives was 1.2%, which was significantly better than that of the comparative example without additives (1.8%). This indicates that the multiple cross-linking function of the additives of the present invention constructs a dense three-dimensional network structure, while the in-situ dehydration function reduces the hydrophilic micropore defects inside the film, effectively reducing the water absorption rate of the material.

[0088] Table 1

[0089] The results showed that the polyimide films obtained in each embodiment exhibited excellent mechanical properties (tensile strength ≥ 168 MPa), good toughness (elongation at break ≥ 30%), high thermal stability (Tg ≥ 272℃, Td5% ≥ 512℃), and excellent insulation properties (dielectric constant ≤ 3.3, dielectric loss ≤ 0.009, water absorption ≤ 1.4%). Compared with the comparative example without aminoimide additives, all properties were significantly improved, indicating that the zwitterionic organic compounds of this application, as additives, can achieve low-temperature and efficient imidization while ensuring the storage stability of polyamic acid slurry, and simultaneously construct a highly cross-linked network and eliminate the adverse effects of dehydration.

[0090] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A zwitterionic organic compound, characterized in that, This includes quaternary ammonium zwitterion structures that are symmetrically located on both sides of the molecular center; The quaternary ammonium zwitterion structure satisfies the following condition: (a) It has a positively charged quaternary ammonium amine center; (b) It has an imide-type negative charge center; (c) It has at least one hydroxyl group.

2. The zwitterionic organic compound according to claim 1, characterized in that, The zwitterionic organic compounds include those represented by the following general chemical formulas: R1R2R3N + -N - -C(O)-R4-C(O)-N - -N + R1R2R3: R1, R2, and R3 are each independently an alkyl group containing a secondary hydroxyl group; R4 is a divalent organic group.

3. The zwitterionic organic compound according to claim 2, characterized in that, R1, R2, and R3 each independently include a C2-C8 alkyl group containing a secondary hydroxyl group, wherein the C2-C8 alkyl group containing a secondary hydroxyl group includes 2-hydroxypropyl, 3-hydroxybutyl, 2-hydroxybutyl, 3-hydroxypentyl, 2-hydroxypentyl, 4-hydroxyhexyl, 3-hydroxyhexyl, 2-hydroxyhexyl, 5-hydroxyheptyl, 4-hydroxyheptyl, 3-hydroxyheptyl, 2-hydroxyheptyl, 6-hydroxyoctyl, 5-hydroxyoctyl, 4-hydroxyoctyl, 3-hydroxyoctyl, and 2-hydroxyoctyl; And / or, the R4 includes C1-C10 alkylene, arylene, and alicyclic groups, wherein the C1-C10 alkylene includes ethylene and propylene, the arylene includes p-phenylene, and the alicyclic group includes cyclohexanedimethyl.

4. The zwitterionic organic compound according to any one of claims 1-3, characterized in that, The zwitterionic organic compounds include those represented by the following chemical formulas: Compound 1: [(HOCH2CH2)2N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 2: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4; Compound 3: [(HOCH(CH2CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4; Compound 4: [(HOCH(CH3)CH2)(HOCH(CH3)CH2)N + (CH2CH3)-N - -C(=O)]2-(CH2)4; Compound 5: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-(CH2)2; Compound 6: [(HOCH(CH3)CH2)2N + (CH3)-N - -C(=O)]2-C6H4; Compound 7: [(HOCH(CH3)CH2CH2)2N + (CH3)-N - -C(=O)]2-(CH2)4.

5. The zwitterionic organic compound according to any one of claims 1-4, characterized in that, The zwitterionic organic compound has thermally reversible decomposition characteristics; And / or; the thermally reversible decomposition temperature of the zwitterionic organic compound is 120℃-180℃; And / or, the thermally reversible decomposition products of the zwitterionic organic compounds include polyhydroxy tertiary amines and diisocyanates.

6. An additive for polyimide, characterized in that, Includes the zwitterionic organic compounds according to any one of claims 1-5.

7. A polyamic acid slurry, characterized in that, Includes the zwitterionic organic compounds according to any one of claims 1-5.

8. The polyamic acid slurry according to claim 7, characterized in that, By weight, it includes: 100 parts by weight of polyamic acid, 0.1 to 15 parts by weight of the zwitterionic organic compound, and 150 to 500 parts by weight of solvent.

9. The polyamic acid slurry according to claim 8, characterized in that, The raw materials for the polyamic acid include dianhydride monomers and diamine monomers. The dianhydride monomers include at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and 4,4'-oxobisphthalic anhydride. The diamine monomers include at least one of 4,4'-diaminodiphenyl ether and p-phenylenediamine. And / or, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

10. A polyimide, characterized in that, It is obtained by curing the polyamic acid slurry according to any one of claims 7-9.